Transport and retention of porous silicon-coated zero-valent iron in saturated porous media - Lu, Haojie; Dong, Jun; Xi, Beidou; Cai, Peiyao; Xia, Tian; Zhang, Mengyue (Environmental pollution (1987), 2021)
Porous silicon-coated zero-valent iron (Fe0@p-SiO2) is a promising material for in-situ contaminated groundwater remediation. However, investigations of factors that affect the transport of Fe0@p-SiO2 remain incomplete. In the present study, Fe0@p-SiO2 composites were prepared by a SiO2-coated technology, and a series of column experiments were conducted to examine the effects of media size, ionic strength, and injection velocity and concentration on retention and transport in saturated porous media. Results showed that the obtained Fe0@p-SiO2 is a core-shell composite with zero-valent iron as the core and porous silicon as the shell. Media size, injection velocity, Fe0 concentration, and ionic strength had a significant impact on the transport of Fe0@p-SiO2. Fe0@p-SiO2 effluent concentrations decreased with a smaller media size. Increasing initial particle concentration and ionic strength led to a decrease in particle transport. High particle retention was observed near the middle of the column, especially with high injection concentration. That was also observable in the condition of lower injection velocity or finer media. The results indicated that two transport behaviors during particles transport, which were “agglomeration-straining” and “detachment-re-migration”. Moreover, the dominated mechanisms for Fe0@p-SiO2 transport and retention in saturated porous media are hydrodynamic dispersion and interception. Given the results, in practical engineering applications, proper injection velocity and concentration should be selected depending on the pollution status of groundwater and the geochemical environment to ensure an effective in-situ reaction zone. [Display omitted] •Transport of SiO2 coated nanoscale zero-valent iron (nZVI) was studied.•Influence of medium size, ionic strength, velocity and concentration was investigated.•SiO2 coated technology seem to be suited method for enhancing nZVI transport.•Hydrodynamic dispersion and interception are main transport and retention mechanisms. The dominated mechanisms for Fe0@p-SiO2 transport and retention in saturated porous media are hydrodynamic dispersion and interception.